Predicting future landslides using remotely sensed imagery: the Langhe Hills in Piemonte, NW Italy. - Mason,PJ; Rosenbaum,MS; Moore,JM (2000)
Existing landslides in the Langhe Hills, NW Italy, have been identified using digital remotelysensed imagery on the basis of their textural and spectral characteristics. Landsat ThematicMapper and multi-temporal SPOT Panchromatic images reveal landslides produced by a stormevent which occurred in 1994, on the basis of key soil properties. High clay content in the soilsand weathered rock profile enhances moisture retention, particularly in hollows and on concaveslopes. Soil moisture assumes the role of a conditioning factor, alongside smectite and ironoxideswhich have been leached from the rocks, and facilitated by groundwater flow throughfractures. Digital images, produced from Landsat TM, representing hydrated mineral (clay), ironoxideand soil moisture content have enabled identification of areas where conditioning factorsare present.